2006
DOI: 10.1073/pnas.0602493103
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial pathology and muscle and dopaminergic neuron degeneration caused by inactivation of Drosophila Pink1 is rescued by Parkin

Abstract: Mutations in Pink1, a gene encoding a Ser͞Thr kinase with a mitochondrial-targeting signal, are associated with Parkinson's disease (PD), the most common movement disorder characterized by selective loss of dopaminergic neurons. The mechanism by which loss of Pink1 leads to neurodegeneration is not understood. Here we show that inhibition of Drosophila Pink1 (dPink1) function results in energy depletion, shortened lifespan, and degeneration of select indirect flight muscles and dopaminergic neurons. The muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

42
728
4
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 730 publications
(775 citation statements)
references
References 42 publications
42
728
4
1
Order By: Relevance
“…This difference may be due to the presence of CG12362, a recent duplicate of ariadne-1 (Marín and Ferrús 2002). On the other hand, parkin mutants are viable, although show some phenotype changes, caused by a general mitochondrial dysfunction (Greene et al 2003;Pesah et al 2004;Clark et al 2006;Park et al 2006;Yang et al 2006). For the other genes, there are no loss-offunction mutants described.…”
Section: Long-term Conservation Of Particular Rbr Genes and Functionamentioning
confidence: 99%
“…This difference may be due to the presence of CG12362, a recent duplicate of ariadne-1 (Marín and Ferrús 2002). On the other hand, parkin mutants are viable, although show some phenotype changes, caused by a general mitochondrial dysfunction (Greene et al 2003;Pesah et al 2004;Clark et al 2006;Park et al 2006;Yang et al 2006). For the other genes, there are no loss-offunction mutants described.…”
Section: Long-term Conservation Of Particular Rbr Genes and Functionamentioning
confidence: 99%
“…Strikingly, most recent studies reveal that abnormal mitochondrial fusion and fission participate in the regulation of apoptosis 5,6 . In particular, they are related to a variety of diseases such as skeletal muscle disorders [7][8][9] , peripheral neuropathy CharcotMarie-Tooth type 2A 10,11 and neurodegeneration 12 .…”
mentioning
confidence: 99%
“…PINK1 mutants share many phenotypic features with parkin mutants [250,251]. Therefore, it was suggested that the two proteins could act in common pathways, with parkin working downstream of PINK1, because transgenic expression of parkin rescued all PINK1 impairments, but not the contrary [243,250,251].…”
Section: Pink1 and Parkinmentioning
confidence: 99%
“…Therefore, it was suggested that the two proteins could act in common pathways, with parkin working downstream of PINK1, because transgenic expression of parkin rescued all PINK1 impairments, but not the contrary [243,250,251]. Goldman et al [252] reported that PINK1 and parkin both play a role in the mitochondrial targeting of autophagy, a process by which the cells degrade intracellular material through lysosomes.…”
Section: Pink1 and Parkinmentioning
confidence: 99%